New records of family Pontellidae (Copepoda: Calanoida) from the northern Arabian Sea - Shumaila Mubarak; Qadeer Muhammad Ali; Hamdy Abo-Taleb (Universitas Malikussaleh, 2026)
This study reports six (06) new records of Pontellidae copepods from northern Arabian Sea of Pakistan: Labidocera kuwaitiana, Labidocera pavo, Labidocera aff. euchaeta, Pontella danae, Pontellopsis herdmani and an unidentified Pontellopsis sp. Specimens were collected from mangrove areas of Shahbunder Creek, Phitti Creek, and Sonmiani Bay during seasonal monsoon intervals from April 2018 to January 2020. Identification was based on morpho-taxonomic examination of appendages using light microscopy and comparison with published taxonomic literature. Voucher specimens deposited in the Marine Reference Collection & Resource Centre, University of Karachi for future references. With these additions, the total number of Pontellidae species known from Pakistan brings the total to 17. The occurrence of species previously documented in the Arabian Gulf and Indian Ocean suggests that seasonal monsoon currents and coastal upwelling may facilitate their dispersal into Pakistani waters. By filling gaps in regional taxonomy, this study highlights the ecological importance of mangrove-associated habitats and emphasizes the need for continued surveys and molecular approaches to better understand copepod diversity and distribution in the northern Arabian Sea.